Wave Attenuation and Dispersion in a 6 mm Diameter Viscoelastic Split Hopkinson Pressure Bar and Its Correction Method - Haotian Zhang; Linjian Ma; Zongmu Luo; Ning Zhang (Shock and Vibration)
The propagation characteristics of viscoelastic waves have been investigated with a 6 mm diameter split Hopkinson pressure bar (SHPB) made of polymethyl methacrylate (PMMA). The strain signals in SHPB tests were improved by the pulse shaping technique. Based on the experimentally determined propagation coefficients, the amplitude attenuation and wave dispersion induced by viscoelastic effects at different impact velocities were quantitatively analyzed. The results indicate that the high-frequency harmonics attenuate faster in a higher phase velocity. With an increase in the impact velocity, the amplitude attenuation of the viscoelastic wave changes slightly during propagation, while the waveform dispersion gradually intensifies. A feasible method by waveform prediction was proposed to verify the validity and applicability of the propagation coefficient. The results indicate that the strain obtained from the small diameter viscoelastic SHPB can be effectively modified by utilizing the propagation coefficient. Furthermore, it is preferred to adopt the propagation coefficient obtained at low impact velocity for correction when the impact velocity varies. Moreover, the PMMA-steel bar impact test was performed to further illustrate the accuracy of the propagation coefficient and the effectiveness of the correction method.